Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,4\left(x-3\right)=7^2-1^3\)
\(4\left(x-3\right)=49-1\)
\(4\left(x-3\right)=48\)
\(\Rightarrow x-3=48:4\)
\(x-3=24\)
\(\Rightarrow x=27\)
\(5x+x=\frac{150}{2}-3\)
\(6x=75-3\)
\(6x=72\)
\(\Rightarrow x=12\)
a, 100 - 7 ( x - 5 ) = 31 + 33
100 - 7 ( x - 5 ) = 31 + 27
100 - 7 ( x - 5 ) = 58
7 ( x - 5 ) = 100 - 58
7 ( x - 5 ) = 42
x - 5 = 42 : 7
x - 5 = 6
=> x = 6 +5
=> x = 11
Vậy x = 11
b, 12 ( x - 1 ) : 3 = 43 + 23
12 ( x - 1 ) : 3 = 64 + 8
12 ( x - 1 ) : 3 = 72
12 ( x - 1 ) = 72 . 3
12 ( x - 1 ) = 216
x - 1 = 216 : 12
x - 1 = 18
=> x = 18 + 1
=> x = 19
Vậy x = 19
c, 24 + 5x = 75 : 73
24 + 5x = 72
24 + 5x = 49
5x = 49 - 24
5x = 25
=> x = 25 : 5
=> x = 5
Vậy x = 5
d, 5x - 206 = 24 . 4
5x - 206 = 16 . 4
5x - 206 = 64
5x = 64 + 206
5x = 270
=> x = 270 : 5
=> x = 54
Vậy x = 54
e, 125 = x3
53 = x3
=> x = 5
Vậy x = 5
g, 64 = x2
82 = x2
=> x = 8
Vậy x = 8
làm mẫu nhé:
a) /4/5 - 1/5x/ - 2/3 = 1/5
=> /4/5 - 1/5x/ = 1/5 + 2/3 = 13/15
=> /4/5 - 1/5x/ = 13/15
/ 4/5 - 1/5x / = -13/15
=> 1/5x = 4/5 - 13/15 = -1/15 => x = -1/15 : 1/5 = -1/3
=> 1/5x = 4/5 - (-13/15) = 5/3 => x = 5/3 : 1/5 = 25/3
còn lại tương tự nha
a, 4.(x-3)=72-13
=> 4(x - 3) = 49 - 1
=> 4(x - 3) = 48
=> x - 3 = 12
=> x = 15
b, 5x+x=150:2+3
=> 6x + = 75 + 3
=> 6x = 78
=> x = 13
a) 4(x-3)=72-13
<=> 4(x-3)=49-1
<=> 4(x-3)=48
<=> x-3=12
<=> x=15
Vậy x=15
b) 5x+x=150:2+3
<=> 6x=75+3
<=> 6x=78
<=> x=13
Vậy x=13
a. 2/3 . ( x + 2 ) = 1/5x
2/3x + 2/3 . 2 = 1/5x
2/3x + 4/3 = 1/5x
2/3x + 4/3 - 1/5x = 0
7/15x + 4/3 = 0
7/15x = -4/3
x = -4/3 . 7/15
x = -20/7
b. x/4 = -2/7
x = -2/7 . 4
x = -8/7.